Manipulation of host immune defenses by effector proteins delivered from multiple secretion systems of Salmonella and its application in vaccine research - Zhou, Guodong; Zhao, Yuying; Ma, Qifeng; Li, Quan; Wang, Shifeng; Shi, Huoying (Frontiers in Immunology, 2023)
Salmonella is an important zoonotic bacterial species and hazardous for the health of human beings and livestock globally. Depending on the host, Salmonella can cause diseases ranging from gastroenteritis to life-threatening systemic infection. In this review, we discuss the effector proteins used by Salmonella to evade or manipulate four different levels of host immune defenses: commensal flora, intestinal epithelial-mucosal barrier, innate and adaptive immunity. At present, Salmonella has evolved a variety of strategies against host defense mechanisms, among which various effector proteins delivered by the secretory systems play a key role. During its passage through the digestive system, Salmonella has to face the intact intestinal epithelial barrier as well as competition with commensal flora. After invasion of host cells, Salmonella manipulates inflammatory pathways, ubiquitination and autophagy processes with the help of effector proteins. Finally, Salmonella evades the adaptive immune system by interfering the migration of dendritic cells and interacting with T and B lymphocytes. In conclusion, Salmonella can manipulate multiple aspects of host defense to promote its replication in the host.